2020
DOI: 10.3389/fnut.2020.558598
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Shaping Inter-individual Differences in Response to Dietary Intakes—A Narrative Review of the Case of Vitamins

Abstract: Recent advances in the field of nutrigenetics have provided evidence on how genetic variations can impact the individuals' response to dietary intakes. An objective and reliable assessment of dietary exposures should rely on combinations of methodologies including frequency questionnaires, short-term recalls or records, together with biological samples to evaluate markers of intake or status and to identify genetic susceptibilities. In an attempt to present current knowledge on how genetic fingerprints contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 115 publications
(189 reference statements)
0
5
0
Order By: Relevance
“…Vitamin B2, for example, is a vital cofactor within the electron transport chain, Krebs cycle, and beta-oxidation (fat burning) ( 45 ), which explained why the increased vitamin B2 intake is a major contributor of BMI reduction. Vitamin B6 and vitamin B12 are involved in one-carbon metabolism, in which MTHFR plays a critical role ( 46 ). Although there is a lack of clear evidence of how promoted one-carbon metabolism is related to weight loss, it is reported that vitamin B intake is positively associated with fat-free mass in overweight/obese females ( 47 ), and according to a meta-analysis with 9,075 participants, higher serum vitamin B12 levels are inversely associated with obesity ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B2, for example, is a vital cofactor within the electron transport chain, Krebs cycle, and beta-oxidation (fat burning) ( 45 ), which explained why the increased vitamin B2 intake is a major contributor of BMI reduction. Vitamin B6 and vitamin B12 are involved in one-carbon metabolism, in which MTHFR plays a critical role ( 46 ). Although there is a lack of clear evidence of how promoted one-carbon metabolism is related to weight loss, it is reported that vitamin B intake is positively associated with fat-free mass in overweight/obese females ( 47 ), and according to a meta-analysis with 9,075 participants, higher serum vitamin B12 levels are inversely associated with obesity ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preeclampsia is characterised by hypertension accompanied by proteinuria in pregnant women over 20 weeks of gestation. This disease can affect both the foetus and the mother and, in extreme situations, can compromise the life of both [47][48][49]. A meta-analysis report by Wang et al (2013) [50] showed a significant association between the MTHFR T allele and pre-eclampsia among Caucasians and people of Asian descent but not among people of African descent.…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, this study showed a higher frequency of reduced vitamin D levels in patients with cirrhosis with or without HCC carrying at least one mutant allele (_/A) for DBP-rs4588 , compared to the control group, in agreement with Santos et al [ 37 ]. There is also a reference to the influence of the polymorphisms of DBP-rs7041 and DBP -rs4588 affecting the binding affinity of DBP with vitamin D, which could consequently influence its anti-tumorigenesis activity [ 41 ]. However, haplotype variations in different ethnicities may contribute to divergences between studies [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%